A Case of Adenomatous Goiter Involving Diffuse, Acute, and Painful Thyroid Enlargement after Fine-Needle Aspiration Cytology - Toshiro Shimo; Katsuhiro Tanaka; Ryohei Ogata; Wataru Saito; Yusuke Ohta; Yoshikazu Koike; Tetsumasa Yamashita; Yutaka Yamamoto; Junichi Kurebayashi (Case Reports in Endocrinology)
The patient was a 44-year-old woman who exhibited a diffuse goiter during health screening. Her medical history did not include any significant medication-based treatment. An echographic examination detected a solid cystic tumor, which measured 21 × 14 × 10 mm, in her right thyroid lobe; however, she displayed normal thyroid function. After fine-needle aspiration cytology had been performed with a 22 G injection needle, the patient immediately complained of compression and pain extending from the front of her neck to her lower chin, which was not accompanied by dyspnea. A second echographic examination revealed diffuse and edematous enlargement and increased internal blood flow in the bilateral thyroid lobes as well as a thyroid nodule. We immediately iced the patient’s neck and administered 125 mg methylprednisolone via an intravenous infusion. Within one hour, her symptoms had markedly improved, but acute pain remained. Thus, we continued the steroid (prednisone) treatment, but the dose was gradually reduced from 10 mg/day to 5 mg/day at 1 week after the patient’s symptoms disappeared. The mechanism responsible for the patient’s condition remains unclear.